You Pose, We Expose – Workshop on Thoracic Imaging Basics and Future Perspectives - Nikolova, S (MAKEDONSKI MEDICINSKI PREGLED –JOURNAL OF MACEDONIAN MEDICAL ASSOCIATION FIRST INTERNATIONAL CONGRESS OF FSA 2022, 2022)
The 20th century was a period of remarkable growth for medicine in general, as well as the field of radiology imaging, when it became a crucial component of the clinical medicine practice. It is expected that radiology will likely continue its exponential growth by interfacing with new realms such as information technology, molecular biology, and by having an essential role in general medical education, biomedical research, and noninvasive therapeutic interventions in the 21st century. Clinical symptoms of patients with different pulmonary diseases tend to be quite similar and further diagnostic work-up includes various tests and most often some kind of imaging. Chest fluoroscopy and radiography were established clinical procedures, soon after the discovery of xrays by Roentgen and the standard chest radiograph remained the pillar of chest imaging for almost 80 years until the emerging of CT and MRI. Thoracic radiology as radiology in general, has endured major changes and advances in both our understanding of the disease and the technology that we apply to its diagnosis. The breakthrough of CT technology from spiral scanning to multidetector and multislice scanning has revolutionized the application of CT. New perspectives have been necessary for conditions as pulmonary nodules follow- up to diagnosis of interstitial lung disease, based on the superior resolution of today's imaging devices. This workshop is centered around educating young medical students the basics of thoracic radiology and provides a thorough analysis of the old and well established chest imaging modules as well as some recent advances in thoracic imaging technology, and discusses new methodologies that may be expected in thoracic radiology over the next decades. The workshop is structured in two main components: basic thoracic radiology lecture with interactive participanceand questions, and interactive thoracic radiology case reporting. First International Congress of FSA, Medicine out of the box 37 Participants will be divided into smaller groups, each able to participate and discuss their opinion on the individual cases in an interactive manner. The curriculum covers almost all aspects of thoracic imaging: obstructive, infectious, interstitial lung disease, small and large airway diseases, mediastinal and vascular pathologies. The main imaging modalities of radiography, computed tomography and magnetic resonance imaging will be addressed within the workshop. The workshop format is well chosen and provides a structured lecture and case-based approach to the various topics and all questions on a topic will be discussed from a radiological and clinical perspective. We can expect further radiology imaging development that will result not only in qualitative improvement of images but also in the capacity to provide both functional data and quantitative evaluation. Such technological advances of the imaging modules will provide more accurate diagnosis and better treatment and will add merit to the radiologic practice. So, future and similar workshop and seminar formats will be essential in obtaining radiology imaging understanding and updated information on imaging technologies for medical students, young clinicians as well as refreshing the knowledge of senior clinicians and radiologist, so that we can all meet the challenges of the fast evolving medicine.